Implementasi Akad Ujrah pada Jasa Pengiriman Barang (Studi Kasus di J&T Express DP Sosa, Kecamatan Sosa) - Lubis, Aminah; Junda Harahap; Nova Indriani Nasution (Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2025)
This research aims: To understand the concept of ujrah from an Islamic economic perspective and to determine the implementation of the ujrah contract in goods delivery services at J&T Express DP Sosa, Sosa District. The research results show that: There are four concepts of ujrah in an Islamic economic perspective that must exist, namely aqid (person who makes a contract), shighat contract, ujroh (wages), and benefits. In delivering goods at J&T Express, DP Sosa has fulfilled several pillars of the contract. For example, people who enter into a contract are required to know the benefits of the goods being contracted so that they can prevent pregnancy. Sighat contract is an expression of the parties entering into the contract here, J&T and the consumer have entered into Sighat Contract with Islamic provisions. Wages can be given to J&T Express DP Sosa for services provided by consumers or customers. Like what consumers do to J&T if they have completed the agreed transaction. The implementation of the ujrah contract on the goods delivery service at J&T Express DP Sosa, Sosa District is in accordance with the ujrah contract. Regarding the estimated time given by J&T Express DP Sosa to consumers when the transaction was first made, this is an estimate or temporary prediction to consumers that the goods will arrive in a certain number of days. However, if the goods do not arrive at the agreed time, this does not damage the ujrah contract between J&T Express DP Sosa and the consumer. The ujrah contract between the two parties remains valid even though the delivery period exceeds the initial agreement. J&T has also informed consumers that delays in package delivery only occur when events occur in online shopping such as in the shoppe, lazada, tokopedia applications, and others.